Penser autrement les ruines : du Tiers paysage rural à la réinvention des communs - Damien Darcis (Interfaces)
In this article, we analyze the concept of rural Tiers paysage (Third landscape) which designates, according to Gilles Clément, neglected rural spaces, abandoned by humans and left fallow, in other words ruins, in which nature recovered it rights. First, we show how this conception of the Tiers paysage, although relatively recent (2004), was already outlined at the end of the 18th century, then took shape throughout the 19th century. While modernity marks the advent of a world structured around, on the one hand, industry and, on the other, nature, the countryside, which does not belong to either of these categories, only acquired the status of landscape on the condition of being "abandoned to nature". Secondly, we identify the fundamental contradiction of this notion of rural Third landscape: if it is the cessation of human activities that makes it possible to define certain rural spaces as Third landscapes, without human intervention, these lose their specificity under the effect of reforestation. Finally, in the third part, we show why this contradiction can be considered as the starting point for a reinvention of the relationship between human and non-human living beings and their territory.